Clinical genomics a guide to clinical next generation sequencing - Kulkarni, Shashikant; Pfeifer, John D. (Elsevier/Academic Press, 2015)
Provides an overview of the various next-generation sequencing (NGS) technologies that are used in clinical diagnostic laboratories. This book focuses on the challenges of diagnostic interpretation of NGS results in a clinical setting